AKTUALISASI DIRI WANITA KARIR YANG MENGURUS RUMAH TANGGA DI GAMPONG KEURAMAT BANDA ACEH - Firmawati Firmawati; Nurul Afany Hasby (Prosiding Seminar Nasional USM, 2019)
This study aims to determine self-actualization in career women who take care of the household. The research method used is a qualitative method with data collection methods in the form of open interviews with semi-structured methods and closed observations. Sampling is done by purposive sampling. There were three research subjects with the following characteristics: women who were married, still had a husband, had one or more children, worked more than 6-8 hours, lived in Keuramat Village, Banda Aceh City. The results showed that women who carried out roles as career women and housewives had different backgrounds in working. Women who have a higher education background can actualize themselves very well at work but are not optimal in taking care of the household. Conversely, women who work because of economic necessity cannot enjoy their work but can actualize themselves by taking care of the household properly.